Effect of Beta-Blocker Therapy on Mortality and Hemodynamic Stability in Septic Shock: A Prospective Observational Study - Sohail Ahmed, Shaista Iftikhar, Zulaikha Malik, Muhammad Amer Mushtaq, Muhammad Zeeshan Alam Khan, Mahjan Rahim (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Septic shock remains a leading cause of mortality in intensive care units, oftencomplicated by persistent tachycardia and hemodynamic instability despite aggressiveresuscitation and vasopressor support.